The Influence of Work Discipline, Workload and Work Environment on the Performance of Air Traffic Controller Employees in the Area Control Center Unit at Airnav Indonesia Jakarta Air Traffic Services Center Branch - Himawan Ariyo Wibowo; Dudung Hadiwijaya; Priyo Susilo (Dinasti Publisher, 2024)
The aim of this research is to determine the magnitude of the influence of Work Discipline, Workload and Work Environment, both partially and simultaneously, on the performance of air traffic controller employees. The method used is associative with a quantitative approach. The number of samples used was 125 respondent, with a simple random sampling technique. Data was taken using a survey method. Data analysis was carried out to test the significance of the hypothesis, coefficient of determination using SPSS V.25 software. The research results show that work discipline, and work environment have a positive and significant effect, both partially. Workload has a negative and significant effect on the performance of air traffic controller employees. As simultaneously, Work discipline, workload and work environment have a positive and significant influence employee work performance in the Area Control Center Unit at Airnav Indonesia Jakarta Air Traffic Services Center Branch.